2014
DOI: 10.1007/s12031-014-0287-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor beta (TNF-β) NcoI polymorphism is associated with multiple sclerosis in Caucasian patients from Southern Brazil independently from HLA-DRB1

Abstract: This study evaluated the association of tumor necrosis factor beta (TNF-β) NcoI polymorphism with the presence of multiple sclerosis (MS), disability, and HLA-DRB1 alleles in 208 Brazilian MS patients. As controls, 147 healthy individuals were included. The disability was evaluated at baseline and 5-year follow-up using the Expanded Disability Status Scale (EDSS). The TNF-β genotypes were determined using PCR and restriction fragment length polymorphism and serum TNF-α level was determined using enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The epidemiological, clinical, and immunological characteristics of the patients with NMO of the present cohort are consistent with previous studies carried out in different population worldwide, such as to be more frequent among women, non-Caucasians, and higher age at onset of disease than the observed among the Brazilian MS cohorts (38,39), as well as other cohorts (37,40,41). The population of the present study showed that a female : male ratio was 21 : 1.…”
Section: Discussionsupporting
confidence: 91%
“…The epidemiological, clinical, and immunological characteristics of the patients with NMO of the present cohort are consistent with previous studies carried out in different population worldwide, such as to be more frequent among women, non-Caucasians, and higher age at onset of disease than the observed among the Brazilian MS cohorts (38,39), as well as other cohorts (37,40,41). The population of the present study showed that a female : male ratio was 21 : 1.…”
Section: Discussionsupporting
confidence: 91%
“…The LTA rs909253 A/G polymorphism has been correlated to the risk of developing several autoimmune diseases, such as scleroderma 12 , multiple sclerosis 13 and systemic lupus erythematosus 5,14 . Single nucleotide polymorphisms (SNPs) of the LTA gene have been suggested to be associated with the susceptibility of AS 15,16 .…”
mentioning
confidence: 99%